THE EFFECT OF PRICE AND PROMOTION ON PURCHASING DECISIONS AT CULINARY BUSINESSES IN AMALI DISTRICT, BONE REGENCY - Sudarmi Sudarmi; Nurhidayanti S; Maulana Maulana; Jumiati Syam (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2024)
Micro, small, and medium enterprises (MSMEs) have experienced rapid growth in Indonesia, leading to a need for development in various sectors such as culinary businesses. A study was undertaken to investigate the impact of Price and Promotion on Purchasing Decisions in culinary establishments in Amali District, Bone Regency. To investigate this relationship, the researchers utilized a quantitative approach, employing a survey method. The data for the study was collected from 139 culinary consumers through questionnaires. The target population for this study was the buyers at culinary establishments in Amali District, Bone Regency. Data analysis consisted of descriptive data analysis and inferential statistics. The findings of the study were quite intriguing. It was discovered that both Price and Promotion have a positive and significant influence on Purchasing Decisions in culinary businesses in Amali District, Bone Regency. This implies that when consumers perceive a reasonable price for the culinary products or services offered and are exposed to effective promotional strategies, they are more likely to make purchasing decisions in favor of these businesses. These findings have important implications for the culinary business owners in Amali District, Bone Regency. They need to carefully consider their pricing strategies and promotional activities to attract and influence customers. By setting competitive and reasonable prices, businesses can enhance their appeal to consumers. Furthermore, implementing effective promotional techniques such as advertising, discounts, and loyalty programs can significantly impact consumer behavior and increase sales.